Semiconductor materials and process technology handbook for very large scale integration (VLSI) and ultra large scale integration (ULSI) - McGuire, G. E. (Noyes Publicatons, 1988)
A broad review of semiconductor materials and process technology, with emphasis on very large-scale integration (VLSI) and ultra large scale integration (ULSI). Brings together "snapshots" of the various aspects in different fields within the technology.
Keywords: Integrated circuits -- Very large scale integration -- Design and construction -- Handbooks, manuals, etc.; elektronické knihy; electronic books